Delivering genetically engineered crops to poor farmers: Recommendations for improved biosafety regulations in developing countries - Falck-Zepeda, José B.; Cavalieri, Anthony J.; Zambrano, Patricia (International Food Policy Research Institute, 2009)
Small-scale, resource-poor farmers in developing countries face daily stresses, including poor soils, drought, and lack of inputs. Ongoing trends such as climate change and population growth will likely exacerbate binding stresses. A new generation of genetically engineered (GE) crop research aims to alleviate these pressures through the improvement of subsistence crops-such as cassava, sorghum, and millet-that incorporate traits such as tolerance to drought, water, and aluminum in soils as well as plants with more efficient nitrogen and phosphor use. However, many developing countries lack the necessary biosafety systems for a timely and cost-effective adoption. This brief focuses on the regulatory reforms necessary for farmers and consumers in developing countries to benefit from GE crops.